Sharing qualitative research
1 online resource (xvi, 282 pages)
Keywords: "In an era of rapid technological change, are qualitative researchers taking advantage of new and innovative ways to gather, analyse and share community narratives? Sharing Qualitative Research presents innovative methods for harnessing creative storytelling methodologies and technologies that help to inspire and transform readers and future research. In exploring a range of collaborative and original social research approaches to addressing social problems, this text grapples with the difficulties of working with communities. It also offers strategies for working ethically with narratives, while also challenging traditional, narrower definitions of what constitutes communities. The book is unique in its cross-disciplinary spectrum, community narratives focus and showcase of arts-based and emerging digital technologies for working with communities. A timely collection, it will be of interest to interdisciplinary researchers, undergraduate and postgraduate students and practitioners in fields including anthropology, ethnography, cultural studies, community arts, literary studies, social work, health and education."--Publisher description